Body Roundness Index Trajectories and the Risk of Cancer: A Cohort Study - Yue Chen; Yiming Wang; Xin Zheng; Tong Liu; Chenan Liu; Shiqi Lin; Hailun Xie; Jinyu Shi; Xiaoyue Liu; Xiangming Ma; Li Deng; Shouling Wu; et al. (Cancer Medicine)
ABSTRACT Background The body rounds index (BRI), an innovative obesity indicator integrating waist circumference (WC) and height, offers a two‐dimensional assessment of obesity. The relationship between BRI trajectories and cancer has been overlooked in previous studies. This study aims to explore the association between BRI trajectories and the incidence of cancer. Methods This study included 42,022 participants with a median age of 48.91 years. Based on the changes in participants' BRI during the period from 2006 to 2010, three BRI trajectory patterns were identified: low‐stable, medium‐stable, and high‐stable. The primary outcome was cancer incidence and the secondary outcome was cancer‐specific deaths. The association between BRI trajectories and cancer incidence and death was explored by cox regression analysis in the total, sex‐specific and age‐specific populations, respectively. Additionally, we further investigated the relationship between BRI and site‐specific cancer incidence. Sensitivity analyses were applied to exclude interferences and ensure the stability of the results. Results After a median follow‐up time of 11.04 years, high‐stable BRI trajectory was significantly associated with increased risk of cancer occurrence compared to low‐stable BRI trajectory. This association was more pronounced in middle‐aged men (men: HR = 1.46, 95% CI = 1.21–1.77, p < 0.001; age < 65: HR = 11.38, 95% CI = 1.15–1.66, p = 0.001). Additionally, high‐stable BRI trajectory was significantly associated with a substantial increase in the risk of site‐specific uterine cancers (HR = 4.92, 95% CI = 1.69–14.33, p = 0.004). Sensitivity analysis confirmed the stability of the results. Conclusion Our study identified a significant association between a high‐stable BRI trajectory and cancer incidence, with this association being most pronounced in middle‐aged men. Moreover, the high‐stable BRI trajectory was strongly associated with uterine site‐specific cancer development. Our findings underscore the importance of implementing lifestyle modifications and monitoring BRI values and their changes to provide effective health guidance.